2014
DOI: 10.1021/jf5004682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical and Enzymatic Modifications on Starch–Stearic Acid Complex Formation

Abstract: Debranched unacetylated and acetylated potato starches with two degrees of substitution, 0.041 (low) and 0.078 (high), combined with or without β-amylase hydrolysis were prepared to form soluble and insoluble complexes with stearic acid. The effects of modifications on the complexation, thermal properties, and X-ray patterns of soluble and insoluble complexes were investigated. Acetylation decreased the recovery of insoluble complexes but increased that of soluble complexes. Low acetylated, β-amylase-treated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
38
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 34 publications
(63 reference statements)
11
38
4
1
Order By: Relevance
“…An additional β‐amylase hydrolysis was used in some of the debranched starch to reduce the molecular mass as described by Arijaje et al . After the debranching, the starch slurry was adjusted to pH 6.5 with 0.5 M NaOH and incubated with 75 µL of β‐amylase at 40°C for 4 h. The enzymatic reaction was terminated by boiling for 15 min, and the β‐amylase‐treated starch was recovered as previously described for the debranched starches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional β‐amylase hydrolysis was used in some of the debranched starch to reduce the molecular mass as described by Arijaje et al . After the debranching, the starch slurry was adjusted to pH 6.5 with 0.5 M NaOH and incubated with 75 µL of β‐amylase at 40°C for 4 h. The enzymatic reaction was terminated by boiling for 15 min, and the β‐amylase‐treated starch was recovered as previously described for the debranched starches.…”
Section: Methodsmentioning
confidence: 99%
“…The complexed stearic acid was analyzed according to the method described by Arijaje et al . Complex (100 mg) was mixed with 10 mL of 1 M HCl and incubated in a boiling water bath with continuous stirring for 1 h. The mixture was cooled and added with 10 mL hexane, and rotated on the rotary shaker for 2 h. Two milliliter of the recovered hexane layer containing the extracted stearic acid was added with 1 mL of boron trifluoride methanol to convert stearic acid to stearic acid methyl esters.…”
Section: Methodsmentioning
confidence: 99%
“…A noticeable decrease in the amount of complexed fenchone was observed for acetylated amylose with a DS 0.43 and greater, presumably because of the destabilization of the helical conformation by the acetylation and an increased steric hindrance. Recently Arijaje et al and Arijaje and Wang demonstrated that acetylation and enzymatic modification of starch increased complex formation of starch with stearic, oleic, and linoleic acids. The formation of soluble complexes between debranched starch with stearic acid increased by 8.3% when starch was acetylated, and increased by 154–245% when the DP was reduced by β‐amylase.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the recovery of insoluble complexes for these fatty acids decreased 23–52% as acetylation was combined with DP reduction. The amount of complexed fatty acids increased as the starch was acetylated and debranched …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation